2023
DOI: 10.1038/s41375-023-02030-8
|View full text |Cite
|
Sign up to set email alerts
|

Ppm1d truncating mutations promote the development of genotoxic stress-induced AML

Monika Burocziova,
Petr Danek,
Anna Oravetzova
et al.

Abstract: Hematopoietic stem cells (HSCs) ensure blood cell production during the life-time of an organism, and to do so they need to balance self-renewal, proliferation, differentiation, and migration in a steady state as well as in response to stress or injury. Importantly, aberrant proliferation of HSCs leads to hematological malignancies, and thus, tight regulation by various tumor suppressor pathways, including p53, is essential. Protein phosphatase magnesium-dependent 1 delta (PPM1D) is a negative regulator of p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…For example, the selective PPM1D inhibitor GSK2830371 suppressed the growth of p53-positive cancer cells in vitro and in animal models. 5 -7 In the present study, Lu and colleagues used a new PPM1B inhibitor (HN252), proved its efficiency in animal models, and elegantly validated its specificity in the Ppm1b CKO animals. 1 , 2 This tool will be invaluable for exploring the functions of PPM1B in several systems.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…For example, the selective PPM1D inhibitor GSK2830371 suppressed the growth of p53-positive cancer cells in vitro and in animal models. 5 -7 In the present study, Lu and colleagues used a new PPM1B inhibitor (HN252), proved its efficiency in animal models, and elegantly validated its specificity in the Ppm1b CKO animals. 1 , 2 This tool will be invaluable for exploring the functions of PPM1B in several systems.…”
mentioning
confidence: 70%
“… 3 In addition, loss of the nuclear PPM1D (also called WIP1) phosphatase caused mTORC-dependent expansion of the HSC compartment in Ppm1d -/- animals, whereas truncating gain-of-function mutations in PPM1D reduced self-renewal of HSC. 4 , 5 Interestingly, the truncated PPM1D stimulates HSC survival after genotoxic stress by inhibiting the p53 pathway and can promote therapy-induced acute myeloid leukemia. 5 , 6 Altogether, these observations point at the crucial role of Ser/Thr phosphatases in the regulation of HSC properties and their potential contribution to the development of hematologic disorders.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The role of Ppm1d mutations in AML development was further corroborated in vivo. While a single dose of γ radiation or two doses of 5-fluorouracil (5-FU) delivered over two weeks failed to initiate leukemia development in Ppm1d mutant mice, sequential treatment with four doses of γ radiation over eight weeks induced eventual AML transformation in a proportion of Ppm1d -mutant mice ( 58 ). These data suggest that malignant transformation depends on cumulative exposures to genotoxic stressors.…”
Section: Genotoxins and Inflammation: The Bm’s Scylla And Charybdismentioning
confidence: 99%
“…Amplification and/or overexpression of PPM1D has been described in a significant number of solid tumors, suggesting a role for PPM1D in carcinogenesis [41][42][43][44]. In addition, studies have shown that the truncated protein products can lead to a relative fitness of hematopoietic cells in the presence of chemotherapy [34,[45][46][47].…”
Section: Introductionmentioning
confidence: 99%